ROUTLEDGE HANDBOOK OF SPORT COMMUNICATION - Pedersen, Paul Mark (ROUTLEDGE, 2024)
The Routledge Handbook of Sport Communication offers a comprehensive and in-depth survey of the contemporary discipline of sport communication. Now in a fully revised and updated second edition, it explores communication within, through, and for sport in various theoretical, conceptual, cultural, behavioral, practical, and managerial aspects. Including contributions from leading sport communication scholars and professionals from around the world, the book is structured around four key themes: theoretical and conceptual foundations; mediated aspects of sport communication; sociological aspects; and organizational, technological, and managerial aspects. This new edition includes expanded coverage of important and emerging topics within sport communication including cross-cultural communication, rhetoric in sport, storytelling, the business of sports broadcasting, athlete activism, and communication within sports teams. Taking stock of current research, new ideas, and key issues, this book is an essential reference for any advanced student, researcher, or practitioner with an interest in sport communication, sport business, sport management, sport marketing, communication theory, journalism, or media studies.
Keywords: Communication in sports -- Handbooks, manuals, etc.; elektronické knihy; electronic books